Contrast Kinetics in CT Coronary Angiography - Singhal, Manphool; Subramanian, Pavithra; Sharma, Arun (Indian Journal of Radiology and Imaging, 2024)
Computed tomography coronary angiography (CTCA) is a technically demanding radiological investigation that requires adequate opacification of coronary arteries at peak aortic enhancement phase, with minimal or no contrast in the superior vena cava and right-sided cardiac chambers to avoid streak artifacts of dense contrast. Therefore, it is prudent to know about contrast media, contrast kinetics, and contrast injection protocols. This article attempts to describe the essentials of various aspects of contrast media that should be considered for CTCA along with an in-depth analysis of contrast kinetics that every radiologist should know for obtaining adequate opacification of coronary arteries.
Keywords: contrast kinetics; CT coronary angiography; time-density curve; peak aortic enhancement; minimum scan delay; test-bolus; bolus-tracking